The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3922/j.psns.2014.008
|View full text |Cite
|
Sign up to set email alerts
|

Blank-comparison matching-to-sample reveals a false positive symmetry test in a capuchin monkey.

Abstract: A positive symmetry test result was obtained with a capuchin monkey that had previously exhibited virtually errorless AB and BA arbitrary matching-to-sample (MTS) with different stimuli. The symmetry test (BA) followed the acquisition of a new AB relation. It seemed possible, however, that the positive result could have occurred through the exclusion of previously defined comparison stimuli and not because the new AB and BA relations had the property of symmetry. To assess this possibility, a blank-comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…While the remaining seven studies report evidence for symmetry in most of the subjects from at least one experiment, the symmetry performances in three studies can be attributed to other variables. The symmetry performance by the monkey in Brino et al (2014) was shown to be a false positive by using tests for select and reject control. In Campos et al (2011), four pigeons showed evidence for symmetry in a simultaneous successive discrimination procedure, but follow‐up tests (Campos et al, 2015) showed that those results could be explained by primary stimulus generalization for all but one pigeon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the remaining seven studies report evidence for symmetry in most of the subjects from at least one experiment, the symmetry performances in three studies can be attributed to other variables. The symmetry performance by the monkey in Brino et al (2014) was shown to be a false positive by using tests for select and reject control. In Campos et al (2011), four pigeons showed evidence for symmetry in a simultaneous successive discrimination procedure, but follow‐up tests (Campos et al, 2015) showed that those results could be explained by primary stimulus generalization for all but one pigeon.…”
Section: Discussionmentioning
confidence: 99%
“…Brino et al (2014) found evidence for symmetry in a capuchin monkey after MET and then explicitly tested for select and reject control. The monkey had an extensive history with simple and conditional discriminations, had shown generalized identity MTS, had learned multiple MTS relations with arbitrary stimuli, and had demonstrated learning through exclusion (Wilkinson et al, 1996).…”
Section: Developments Since 2007mentioning
confidence: 99%
“…). Raul (M14), Dracula (M13) and Tico (M23) had extensive experimental histories of training in simple and conditional discrimination (Brino et al, ; Galvão et al, ; Man et al, ); Tico and Dracula had additional histories of training of tool usage (Delage, ). Raul (M14) had also been exposed to the gradually increasing delays and ITIs within arbitrary matching training (Costa, ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, a more recent experiment has examined symmetry after MET in a capuchin monkey with an extensive history of MTS training yielding generalized identity matching, but also with previous failures to show symmetry (Brino et al, 2014a;Brino, Campos, Galvão, & McIlvane, 2014b). Three arbitrary (AB) relations were trained in a simultaneous MTS procedure along with two reversed (BA relations).…”
Section: Met and Derived Stimulus Relations In Animalsmentioning
confidence: 99%
“…However, there are significant procedural limitations in these studies that may have hindered an effective demonstration of emergent symmetry. For example, only six or fewer exemplars were trained in most of the studies (Brino et al, 2014a(Brino et al, , 2014bLionello-DeNolf & Urcuioli, 2002;Velasco et al, 2010;Yamamoto & Asano, 1995). Of course there is no real way to know how many exemplars of reinforced symmetry might be needed to produce AARR.…”
Section: Met and Derived Stimulus Relations In Animalsmentioning
confidence: 99%